Cytosolic ppGpp accumulation induces retarded plant growth and development. (1st February 2016) - Ihara, Yuta; Masuda, Shinji
ABSTRACT: In bacteria a second messenger, guanosine 5′-diphosphate 3′-diphosphate (ppGpp), synthesized upon nutrient starvation, controls many gene expressions and enzyme activities, which is necessary for growth under changeable environments. Recent studies have shown that ppGpp synthase and hydrolase are also conserved in eukaryotes, although their functions are not well understood. We recently showed that ppGpp-overaccumulation in Arabidopsis chloroplasts results in robust growth under nutrient-limited conditions, demonstrating that the bacterial-like stringent response at least functions in plastids. To test if ppGpp also functions in the cytosol, we constructed the transgenic Arabidopsis expressing Bacillus subtilis ppGpp synthase gene yjbM . Upon induction of the gene, the mutant synthesizes ∼10–20-fold higher levels of ppGpp, and its fresh weight was reduced to ˜80% that of the wild type. These results indicate that cytosolic ppGpp negatively regulates plant growth and development.